2018
DOI: 10.1177/1060028018817935
|View full text |Cite
|
Sign up to set email alerts
|

Common Bacterial and Viral Infections: Review of Management in the Pregnant Patient

Abstract: Objective: To review the treatment of common bacterial and viral infections occurring in the pregnant patient. Data Sources: A literature search of MEDLINE was performed (inception to October 2018). The Centers for Disease Control and Prevention website was utilized for additional information. Study Selection and Data Extraction: Relevant English-language studies and those conducted in humans were considered. Data Synthesis: β-Lactams alone or in combination are the preferred treatment for many common infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 86 publications
(185 reference statements)
0
44
0
Order By: Relevance
“…Severe forms, however, have also been described in young women [ 3 ]. It is known that pregnancy is a state of special immune tolerance that predisposes women to viral infection [ [4] , [5] , [6] ]. Extensive population-based cohort studies have shown that seasonal influenza epidemics place pregnant women at increased risk of severe complications [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Severe forms, however, have also been described in young women [ 3 ]. It is known that pregnancy is a state of special immune tolerance that predisposes women to viral infection [ [4] , [5] , [6] ]. Extensive population-based cohort studies have shown that seasonal influenza epidemics place pregnant women at increased risk of severe complications [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, age significantly affect the severity of infection, e.g., school-age children found to be least affected age group than the young adults and older ones ( Kang and Jung, 2020 ). Moreover, pregnant women also found to be more severely affected from viral infections related to physiological changes occurring during pregnancy ( Rac et al, 2019 ). During epidemics including SARS, MERS, and recent new coronavirus infection pandemic i.e., COVID-19, several surveillance studies confirmed more severe illness in pregnant woman than general population.…”
Section: Severity Of Infectious Diseasesmentioning
confidence: 99%
“…With antibiotic resistance to erythromycin, clindamycin, and cefazolin on the rise, definitive antibiotic therapy should be based on culture and guided by the sensitivity pattern. [37][38][39] Although nitrofurantoin typically has been avoided in the fi rst trimester due to potential risk of birth defects, it may Antibiotics for treatment of GBS bacteriuria in pregnancy 21,[34][35][36]…”
Section: Newer Retrospective and Prospective Studies Have Not Demonstrated A Higher Risk Of Preterm Birth In Individuals With Gbs Bacterimentioning
confidence: 99%
“…be prescribed in the second and early third trimesters. 35,37 Nitrofurantoin and trimethoprim/sulfamethoxazole should be avoided after 36 weeks gestational age when they may increase neonatal jaundice and predisposition to kernicterus if taken in the last week before delivery. 35 Additionally, nitrofurantoin has been associated with a low risk of fetal or neonatal hemolytic anemia if the mother has glucose-6-phosphate deficiency.…”
Section: Penicillin Is the Antibiotic Of Choice For Gbs In Nonallergic Individuals And Antibioticmentioning
confidence: 99%
See 1 more Smart Citation